2016
DOI: 10.1111/bph.13439
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the first in class clinical candidate PF‐05190457: a selective ghrelin receptor competitive antagonist with inverse agonism that increases vagal afferent firing and glucose‐dependent insulin secretion ex vivo

Abstract: BACKGROUND AND PURPOSEGhrelin increases growth hormone secretion, gastric acid secretion, gastric motility and hunger but decreases glucose-dependent insulin secretion and insulin sensitivity in humans. Antagonizing the ghrelin receptor has potential as a therapeutic approach in the treatment of obesity and type 2 diabetes. Therefore, the aim was to pharmacologically characterize the novel small-molecule antagonist PF-05190457 and assess translational pharmacology ex vivo. EXPERIMENTAL APPROACHRadioligand bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…The ghrelin ED 50 was determined in this study to be lower than the literature-reported 5 pmol kg -1 min -1 , and the ghrelin infusion rate of 1 pmol kg -1 min -1 was found to better approximate the ED 50 . As expected, PF-05190457 dosedependently inhibited the ghrelin-induced GH with a maximum inhibition observed at a 100 mg PF-05190457 BID, which achieved maximum free concentrations of approximately 18-fold the human K i [57,69].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The ghrelin ED 50 was determined in this study to be lower than the literature-reported 5 pmol kg -1 min -1 , and the ghrelin infusion rate of 1 pmol kg -1 min -1 was found to better approximate the ED 50 . As expected, PF-05190457 dosedependently inhibited the ghrelin-induced GH with a maximum inhibition observed at a 100 mg PF-05190457 BID, which achieved maximum free concentrations of approximately 18-fold the human K i [57,69].…”
Section: Discussionsupporting
confidence: 78%
“…Ex vivo, ghrelin decreases glucose-induced insulin release in rodent islets and perfused pancreas [22,24,25,71,72]. PF-05190457 increased intracellular calcium within rat dispersed islets and increased insulin secretion from human islets ex vivo in a glucose-dependent manner [57,69]. However, PF-05190457 did not act as an insulin secretagogue in healthy volunteers as postprandial insulin was not modulated.…”
Section: Figurementioning
confidence: 96%
“…Pfizer recently developed a GHSR1a receptor antagonist, PF-05190457, that is currently in clinical evaluation for the treatment of T2D. This drug shows beneficial effect on glucose-dependent insulin secretion in vitro , and increases insulin secretion in isolated human islet [ 137 , 138 ]. Interestingly, PF-05190457 was stopped after the phase I clinical trials but nor for safety reasons [ 139 ] and it remains in clinical evaluation for the treatment of insomnia [ 140 ].…”
Section: Clinical Studies On Ghrelins Role In Glucose Metabolismmentioning
confidence: 99%
“…Interestingly, vagal afferent nerve firing is decreased by signals that increase alcohol intake, such as ghrelin (Date et al, 2002), whereas it is increased by blockade of peripheral ghrelin receptors (Kong et al, 2016) or by cholecystokinin (Date et al, 2002; Schwartz et al, 1997), which also reduces alcohol intake (Geary et al, 2004). The apparent reciprocal relationship between vagal afferent nerve firing and alcohol preference is compatible with the increased incidence of alcoholism following Roux‐en‐Y gastric bypass surgery, which disrupts gastric innervation (Hajnal et al, 2012), and results in loss of ghrelin regulation of the firing of VTA dopaminergic neurons (Sirohi et al, 2017).…”
Section: Therapeutic Potential Of Cb1r Blockade In Alcoholismmentioning
confidence: 99%